2022
DOI: 10.1182/blood.2021012295
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils in acute inflammation: current concepts and translational implications

Abstract: Modulation of neutrophil recruitment and function is crucial for targeting inflammatory cells to sites of infection to combat invading pathogens while at the same time limiting host tissue injury or autoimmunity. The underlying mechanisms regulating recruitment of neutrophils, one of the most abundant inflammatory cells, have gained increasing interest over the years. The previously described classical recruitment cascade of leukocytes has been extended to include not only capturing, rolling, adhesion, crawlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 182 publications
0
38
0
Order By: Relevance
“…In general, neutrophils are promptly recruited into the site of infection, and neutrophilia is common at the very early phase of viral infections [ 48 , 49 ]. Indeed, neutrophils are the first-line immune cells in the acute phase of most infections (bacteria, viruses, and fungi) [ 50 , 51 ] and other non-infectious inflammatory conditions [ 52 ]. In most viral infections, neutrophil numbers peak during the early phase of infections, follow by neutrophil reduction and lymphocyte elevation (lymphocytosis).…”
Section: Discussionmentioning
confidence: 99%
“…In general, neutrophils are promptly recruited into the site of infection, and neutrophilia is common at the very early phase of viral infections [ 48 , 49 ]. Indeed, neutrophils are the first-line immune cells in the acute phase of most infections (bacteria, viruses, and fungi) [ 50 , 51 ] and other non-infectious inflammatory conditions [ 52 ]. In most viral infections, neutrophil numbers peak during the early phase of infections, follow by neutrophil reduction and lymphocyte elevation (lymphocytosis).…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation of endothelial cells, the interaction between upregulated P-selectin, L-selectin, E-selectin, P-selectin glycoprotein ligand 1, E-selectin ligand or s-Lex expressed on leukocytes mediates the binding and rolling of leukocytes, which is a prerequisite for cell migration [ 72 ]. Interestingly, Rüster et al found that MSCs bind to endothelial cells in a P-selectin-dependent manner [ 73 ].…”
Section: Mechanisms Of Msc Homingmentioning
confidence: 99%
“…Sepsis evokes the extravasation of leukocytes and consumption of platelets [ 39 , 40 ]. Such events demand replenishing and mobilization of cellular pools to outweigh cellular deficiencies within the circulation [ 40 ].…”
Section: Mechanisms Of Immune Cell Phenotype Switching: Outside In An...mentioning
confidence: 99%
“…Sepsis evokes the extravasation of leukocytes and consumption of platelets [ 39 , 40 ]. Such events demand replenishing and mobilization of cellular pools to outweigh cellular deficiencies within the circulation [ 40 ]. HSCs express Toll-like receptors, which trigger myeloid differentiation and aid in replenishment of innate immune cells during infection [ 41 ].…”
Section: Mechanisms Of Immune Cell Phenotype Switching: Outside In An...mentioning
confidence: 99%
See 1 more Smart Citation